Scaffold Remodelling of Diazaspirotricycles Enables Synthesis of Diverse sp 3 ‐Rich Compounds With Distinct Phenotypic Effects - Okolo, Ephraim A.; Pahl, Axel; Sievers, Sonja; Pask, Christopher M.; Nelson, Adam; Marsden, Stephen P. (Chemistry : a European journal, 2023)
A ‘top down’ scaffold remodelling approach to library synthesis was applied to spirotricyclic ureas prepared by a complexity‐generating oxidative dearomatisation. Eighteen structurally‐distinct, sp 3 ‐rich scaffolds were accessed from the parent tricycle through ring addition, cleavage and expansion strategies. Biological screening of a small compound library based on these scaffolds using the cell‐painting assay demonstrated distinctive phenotypic responses engendered by different library members, illustrating the functional as well as structural diversity of the compounds.